Open source technologies for delivering historical maps online - case studies at the National Library of Scotland - Fleet, Christopher; Pridal, Petr (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
Over the last four years, the National Library of Scotland has saved money and improved user access to online historical maps through the implementation of new open source technologies. These new tools include a new Viewer for MrSID images using OpenLayers, a collaborative Georeferencer application, new Tile Map Services for delivering georeferenced historical maps online, and a new GeoServer and OpenLayers application for accessing 44,000 series maps as clickable indexes. All of these applications were developed by Petr Pridal / Klokan Technologies, in collaboration with the National Library of Scotland, and all of them are easily extendible to other map libraries. These open source tools also provide an excellent basis for collaboration with other map libraries, sharing technology, experience and advice.